5-HTTLPR polymorphism is associated with nostalgia proneness: The role of neuroticism. (4th March 2019) - Luo, Yu L. L.; Welker, Keith M.; Way, Baldwin; DeWall, Nathan; Bushman, Brad J.; Wildschut, Tim; Sedikides, Constantine
ABSTRACT: Nostalgia, a sentimental longing for the past, is a self-relevant and social emotion. Nostalgia proneness is associated with alleviation of distress or instability (e.g., neuroticism). Although nostalgia proneness is heritable, the specific molecular contributors to this heritability are unknown. We focused on a polymorphism in the promoter of the serotonin transporter gene (5-HTTLPR) as a possible biological basis of nostalgia proneness, because the serotonin system has been associated with sensitivity to negative experience. Participants ( N = 397 adults) who had reported levels of nostalgia proneness were genotyped. A subsample also completed a measure of neuroticism. Participants with the 5-HTTLPR short allele were higher on nostalgia proneness than those without this allele. Neuroticism mediated the relation between 5-HTTLPR and nostalgia proneness. These findings enrich our understanding of the genetic and personality underpinnings of nostalgia.